Analisis likuiditas dan rentabilitas untuk menilai kinerja keuangan pada pt. Indocement tunggal prakarsa, tbk tahun 2006 – 2010 - Raswan Udjang (Universitas Mercu Buana Yogyakarta, 2013)
The purpose of this study is to analyze the financial performance of companies using the method of Liquidity Ratios (Current Ratio and Quick Ratio = CR = QR) and Profitability (Gross Profit Margin = GPM, NPM = Net Profit Margin, Operating Income Margin = OIM, Return on Assets = ROA, Return on Equity = ROE).The research methodology in this study specifically to collect financial data of PT. Indocement Tunggal Perkasa Tbk through secondary data obtained from the download in the financial statements http://www.indocement.co.id period / year from 2006 to 2010. Analysis tools are used to analyze financial performance using ratios Liquidity and Profitability.The results of this study indicate that the PT. Indocement, Tbk has good financial performance, using indicators Liquidity and Profitability with quantitative values as follows: In 2006, CR, QR, GPM, NPM, OIM, ROA, ROE, respectively: 2,15;0,97 ; 2,42; 0,67; 1.20; 0.46, and 0.32. In 2007, CR, QR, GPM, NPM, OIM, ROA, ROE, respectively: 2.96; 1.65; 2.90; 1.04; 1.67; 0.10, and 0.53. In 2008, CR, QR, GPM, NPM, OIM, ROA, ROE, respectively: 1.79; 1.01; 3.09; 1.34; 1.89; 0.15, and 0.95. In 2009, CR, QR, GPM, NPM, OIM, ROA, ROE, respectively: 3.01; 2.29; 4.39; 2.36; 3.18; 0.21, and 1.49. Years 2010, CR, QR, GPM, NPM, OIM, ROA, ROE, respectively: 5,56; 4,59,3; 29,2; 64, 3.29; 0.21, and 1.75. Results of this study can be concluded that, the financial performance. Indocement, Tbk can be good.